Respuesta :

Answer:

Part 1) [tex]m\angle Z=tan^{-1}(\frac{14}{6})[/tex]

Part 2) [tex]m\angle Y=tan^{-1}(\frac{6}{14})[/tex]

Step-by-step explanation:

Part 1) Find the measure of angle Z

we know that

In the right triangle XYZ of the figure

The tangent of the angle Z is equal to divide the opposite side to angle Z by the adjacent side to angle Z

so

[tex]tan(Z)=\frac{XY}{XZ}[/tex]

substitute the given values

[tex]tan(Z)=\frac{14}{6}[/tex]

[tex]m\angle Z=tan^{-1}(\frac{14}{6})[/tex]

Part 2) Find the measure of angle Y

we know that

In the right triangle XYZ of the figure

The tangent of the angle Y is equal to divide the opposite side to angle Y by the adjacent side to angle Y

so

[tex]tan(Y)=\frac{XZ}{XY}[/tex]

substitute the given values

[tex]tan(Y)=\frac{6}{14}[/tex]

[tex]m\angle Y=tan^{-1}(\frac{6}{14})[/tex]